Konsep Harta Bersama Suami Istri Dalam Fiqh Munakahat - Musfira, Musfira; Syarif, Muhammad (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The joint property of husband and wife so far in Islamic law is not known, even in Islam the husband's property belongs to the husband as well as the wife's property. Even the husband is obliged to provide for his wife both physically and mentally as much as the husband. So far, common property in Islamic law has been more analogous to shirkah. While shirkah is not the realm of munakahat fiqh but in the realm of muamalah fiqh (buying and selling). So it requires a more in-depth study in analyzing the concept of joint property between husband and wife in fiqh munakahat. This study uses a method of writing content analysis descriptions with a normative juristic approach and 'urf. As for the data collection, this study uses primary legal data, secondary legal data and tertiary legal data. This research results in the conclusion that the concept of joint property of husband and wife in fiqh munakahat is a consequence of a right and obligation that has implications for inheritance that is tied to a sacred marriage contract, because marriage is a lifelong covenant bond before Allah that will be held accountable someday.